E- Agriculture leads to rural development in India: A Review - Thakur, Nidhi (The journal of contemporary issues in business and government, 2021)
The United Nations' Food and Agriculture Organization (FAO) has developed an e-agriculture plan in partnership with the International Telecommunication Union to assist countries in using information and communication technologies to support rural development. Information and communication technologies (ICTs), which are mostly focused on agriculture, can assist enhance agricultural growth by enhancing farmers' access to essential information, allowing them to make the best decisions and manage their resources responsibly. In this era of climate change, when extreme weather occurrences are the norm, e-agriculture can provide services such as weather forecasts and disaster alerts that can assist farmers in making informed decisions. Agriculture has evolved into a knowledge-intensive industry, and having access to the appropriate information at the right time can make all the difference in a small-holder farmer's livelihood. Governments can supply rural communities with weather, market pricing, and insurance information that adds to their livelihoods with the correct kind of ICT services. Many of the challenges in the agricultural sector can be solved by having access to the correct information. Disaster planning and management, including measures like wise water management, watershed upkeep, and reliable meteorological information, can go a long way toward mitigating the effects of weather and climate change. Developed countries are already implementing a variety of agricultural technologies. Small-holder farmers in underdeveloped nations benefit from e-agriculture because it makes technology more accessible and affordable. Simple technology, such as soil health analysis, can assist a farmer in determining the sort of fertilizer to use in his land. Another excellent idea is to connect farmers with markets by providing market information and assisting them in receiving electronic payments.Initiatives like E-Choupal have proved the power of bringing communities together in India, A strategic approach to integrating the growth and reach of ICTs in other industries such as banking, insurance, and mobile technologies for agriculture is essential for identifying crucial services and solutions and ensuring their long-term viability.This research investigates the possible contribution of e-agriculture to the development of rural areas and the improvement of farmers' livelihoods.